Study on the particle stratification and penetration of a swing vibrating screen by using DEM. Issue 3 (30th September 2019) - Ning, Shuigen; Xiao, Jianzhang; Wang, Guifeng; Huang, Pengcheng
Abstract : Purpose: As for vibrating screen, the separation of granular materials is a very complicated process, particularly the screening with a swing trace. To study the characteristics of stratification and penetration in the swing vibrating screen, a three-dimensional numerical model was developed to simulate the screening process. Design/methodology/approach: The discrete element method (DEM) was used to perform the numerical simulation, and the kinetic model of the swing screening was established. The regions of stratification and penetration were defined, and the mathematical functions relating fine particle ratio of stratification and penetration to time were presented using the least squares method. Findings: The results show that the low value of frequency (5 and 10 Hz) has a limited effect on the stratification, while the obvious effect can be found at high frequency. A low frequencies or small swing angles may enhance the particle penetration. By studying the vibration parameters affecting the stratification and penetration rate, it is found that the frequency has more influence than the swing angle. Originality/value: The higher screening efficiency and processing capacity can be further obtained for the swing vibrating screen by comparing with the linear vibrating screen. These results reveal the fundamental characteristics of particle motion in the swing screening, which will provide reliable guidance for studying the design optimization of vibrating screen.